Before and after gender: sexual mythologies of everyday life (2016)
The purpose of this book is to apply some of the findings of social anthropolo- gists to a topic which they do not often treat on its own, male-female relations. It is intended to suggest a point of view rather than offer an original synthesis, and the ideas in it are drawn from many sources in addition to those specifically given reference. But although the point of view is one which an anthropologist might be expected to follow, it in no way amounts to an orthodoxy. At the same time, I have both taken much anthropological analysis for granted and been free with the material I quote. I hope the authors whose works I cite will find there has not been too much distortion. Several parts of the book were written in collaboration with Joyce Evans, my mother. I thank her for her help in this way, especially for the reading she did and for perusing the manuscript. Joyce Evans has for many years lectured on women’s roles and “the woman question” to historical studies and literature classes, and any perspective I can lay claim to on the topic derives largely from what she has taught me.